In pursuit of the millennium: Judeans and their land - Cromhout, M. (Acta Theologica, 2007)
This article aims to indicate the importance of the concept “land” with regard to the nature of Judean ethnic identity. It shows from evidence in the Bible and contemporary literature how Yahweh, the people, and the land belonged together. In this article events from the Maccabean Revolt onwards are recounted to illustrate how much was based on the Judean claim and attitude to the land. The article also illustrates that the concept “land” had been the central focus of eschatological expectations as witnessed by the investigation of the relevant documents.